China, India, and the Socioeconomic Determinants of Their Competitiveness. (22nd August 2010) - Grupe, Claudia; Rose, Axel
Abstract : We analyze and compare the social, cultural and historical determinants that influence the international competitiveness of China and India. Starting with the discussion why pure economic determinants cannot solely explain a country's competitiveness, we will analyze previous qualitative research and evaluate quantitative data to assess which country has more favorable socio-economic factors influencing its economic performance in the long run.